2014
DOI: 10.1016/j.drugalcdep.2013.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Age, period and cohort trends in drug abuse hospitalizations within the total Swedish population (1975–2010)

Abstract: Background: The societal consequences of drug abuse (DA) are severe and well documented, the World Health Organization recommending tracking of population trends for effective policy responses in treatment of DA and delivery of health care services. However, to correctly identify possible sources of DA change, one must first disentangle three different time-related influences on the need for treatment due to DA: age effects, period effects and cohort effects. Methods: We constructed our main Swedish national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 38 publications
6
22
0
Order By: Relevance
“…No additional covariates were included in the age-period-cohort models, since no potential confounders were identified using a directed acyclic graph (Bandoli, Palmsten, Flores, & Chambers; Williamson et al). This approach is consistent with previous age-period-cohort analysis of substance use (Giordano et al, 2014; W. C. L. Kerr, C.; Ye, Y., 2017; Miech & Koester, 2012; Piontek, Kraus, & Pabst, 2011).…”
Section: Methodssupporting
confidence: 88%
“…No additional covariates were included in the age-period-cohort models, since no potential confounders were identified using a directed acyclic graph (Bandoli, Palmsten, Flores, & Chambers; Williamson et al). This approach is consistent with previous age-period-cohort analysis of substance use (Giordano et al, 2014; W. C. L. Kerr, C.; Ye, Y., 2017; Miech & Koester, 2012; Piontek, Kraus, & Pabst, 2011).…”
Section: Methodssupporting
confidence: 88%
“…However, a recent study of drug abuse in Sweden over four decades revealed that from 1997–2010, period and cohort effects on hospitalisations due to drug abuse have remained relatively stable (48). …”
Section: Discussionmentioning
confidence: 99%
“…Second, we have previously shown evidence for increased rates of DA in Sweden over the time period of our study (Giordano et al, 2013). We therefore explored whether incorporating these effects into our structural models would impact our parameter estimates.…”
Section: Discussionmentioning
confidence: 63%